Total Ecosystem Carbon Stocks of Mangroves in Lamu, Kenya; and Their Potential Contributions to the Climate Change Agenda in the Country - Kairo, James; Mbatha, Anthony; Murithi, Martin M.; Mungai, Fredrick (Frontiers in Forests and Global Change, 2021)
Mangroves are carbon-rich ecosystems found in tropical and subtropical areas of the world. However, they are threatened by a combination of natural and human-induced factors. The current study assessed mangrove cover and cover change, as well as measuring carbon stocks and emission potentials of mangroves in Lamu, Kenya. We sampled above and below-ground carbon pools, including soil organic carbon, in 152 plots distributed throughout the study area. The total carbon stock of mangroves in Lamu was estimated at 20 million Mg C, with an average density of 560.22 ± 64.26 Mg C ha-1. Southern swamps recorded significantly higher carbon densities (p < 0.05) than other mangrove management blocks in Lamu. At least 1,739 ha of mangroves in Lamu were lost between 1990 and 2019 due to anthropogenic activities, representing a decline of 60 ha yr-1. Total emissions from loss and degradation of mangroves in Lamu is estimated at 140.1 Mg C ha-1; which translates to 30,840.1 Mg tCO2e yr-1. Assuming an offset price of US$10/ Mg CO2e, the estimated costs of avoided emissions in Lamu is US$308,401 yr-1 plus other co-benefits such as fishery functions and shoreline protection. Mainstreaming mangroves and associated blue carbon ecosystems into national development and climate change agenda could accelerate Kenya’s achievements of both Sustainable Development Goals (SDGs) and the Paris Agreement.